Case Report: Phenotype-Gene Correlation in a Case of Novel Tandem 4q Microduplication With Short Stature, Speech Delay and Microcephaly - Umlai, Umm-Kulthum Ismail; Haris, Basma; Hussain, Khalid; Jithesh, Puthen Veettil (Frontiers in Endocrinology, 2022)
We describe a sporadic case of a pure, tandem, interstitial chromosome 4q duplication, arr[hg19] 4q28.1q32.3 (127,008,069-165,250,477) x3 in a boy born at 36 weeks of gestation. He presented with microcephaly (head circumference <1st percentile), short stature (height <2nd percentile) and poor weight gain (weight <3rd percentile). Hypospadias and horseshoe shaped kidneys were also revealed following a urinary tract ultrasound. Biochemical analysis revealed normal growth hormone and thyroid hormone levels. While gross and fine motor skill development was in line with his age, speech delay was observed. This patient adds to a group of more than 30 cases of pure 4q tandem duplication with common and differing phenotypic presentations. Using a retrospective analysis of previous case studies alongside the current case and bioinformatics analysis of the duplicated region, we deduced the most likely dosage sensitive genes for some of the major phenotypes in the patient. The positive predictive value (PPV) was calculated for each gene and phenotype and was derived by comparing the previously reported patients who have gene duplications and an associated phenotype versus those who had the gene duplications but were unaffected. Thus, the growth retardation phenotype may be associated with NAA15 duplication, speech delay with GRIA2 and microcephaly with PLK4 duplication. Functional studies will help in confirming the observations and elucidating the mechanisms. However, our study highlights the importance of analysing case reports with pure duplications in defining phenotype-gene relationships and in improving our knowledge of the function of precise chromosomal regions.